(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The right to food in India is recognised as an essential component of the fundamental "right to life" as stated in Article 21 of the Indian Constitution. The Supreme Court has also acknowledged in several decisions that the "right to life" should be understood as the right to live with human dignity. It is also connected to Articles 39(a) and 47 within the Directive Principle of State Policy. The National Food Security Act was implemented on July 5th, 2013, with the aim of guaranteeing food security and affordable access to all beneficiaries, enabling them to live a dignified life. The Policy, as stipulated by the Act, aims to grant a lawful entitlement to subsidised food grain to specific beneficiaries. The concurrent evaluation process was initiated in 2018 with the assistance of the Ministry of Consumers, Food and Public Distribution and the Department of Food and Public Distribution. Its purpose is to assess the implementation of the Act and identify challenges that arise at the ground level. Additionally, it aims to develop innovative mechanisms to address these challenges. The district of Mohali, located in Punjab, has been chosen as the study site for the initial concurrent evaluation. This district serves as the foundation for the research paper. A type of mixed research methodology has been employed. A total of 75 samples were gathered at the beneficiary level, 10 samples at the fair price shop (FPS) level, and 1 sample at the Go down level. The results have been generated using the Statistical Package for the Social Sciences Software. The conclusions and recommendations are derived from the software’s outcomes, as well as inferences drawn from the field survey. This study intends to accurately assess the execution of provisions outlined in the Act, evaluate their effectiveness at the beneficiary level, and observe the realisation of the ’legal right to food’ in the study region.